A study on the relationship between organizational learning and organizational commitment at Pejabat Pendidikan Daerah Lipis (PPDL) / Nurulain Athirah Isa - Isa, Nurulain Athirah (Faculty of Business and Management, 2019)
The researcher conducted a study on the relationship between organizational learning and organizational commitment at Pejabat Pendidikan Daerah Lipis (PPDL) Kuala Lipis, Pahang. Developing, pertaining and transforming knowledge within the organization is known as organizational learning. In this study, there were four independent variables under organizational learning namely motivation, leadership, innovation and teamwork. Meanwhile, the dependent variable was organizational commitment. Organizational commitment was the psychological status that an individual has to achieve about goals and motivation. It was important to the organization in order to find out their loyalty and they are being committed to the organization or not through their performances. The method used in this study was correlation research. Correlational research was used to examine the relationship _ between these variables. The questionnaires have been handed to 65 copies of respondents. A simple random technique has been used in this study. Besides, the data collected using Statistical Package for Social Science (SPSS). The results of the data were presented using descriptive statistic, standard deviation and mean, and correlation coefficient. Meanwhile, for conclusion and recommendation, the researcher concluded that between these four independent variables under organizational learning, the researcher found that innovation has the strong relationship towards organizational commitment at this organization (r.647, p>005). The researcher recommended of that the studies for further investigation should be conducted on different organization such as private sector so that they can get strong and validate findings of this study.